Estudio de mejora en la producción y comercialización de válvulas para cilindros de GLP 10 kg en Ememsa - Vargas Quispe, Cristhian (2021)
The present research is a study of production improvement and commercialization of the valves for 10 Kg LPG cylinders in Empresa Metalmecánica S.A. (EMEMSA). The research began with a request from senior management to carry out the study due to a reduction in the demand of valves. Using a cause effect diagram and the Pareto chart, it was identified that the heavy valve design was the cause of the problem, which had an impact on the high cost and price. Once the cause had been identified, it was decided to redesign the valve body taking into account that the parameters of 360.0009-1 Standard had to be complied. After redesigning and manufacturing the valves, it was possible to reduce the production cost, since the valve that weighed 0.283 Kg now weighs 0.210 Kg, reaching a reduction of weight of 0.073 Kg per valve, thereby reducing the cost; also achieving savings of S/ 676,896 with an investment of S/ 16,000, only in the first year. The project also presents the production process and laboratory tests to which the valves are subjected to demonstrate compliance with the NTP 360.009-1 standard. DOP diagrams are used for its development. The demand was recovered due to the implementation of the project. In recent years (2013 and 2014) the annual demand was approximately 200,000 valves, after carrying out the solution only in the first year, the demand increased to more than 300,000 valves per year, that is, more than 50% and in the following years it exceeded 400,000 valves per year. Finally, through statistical tables, the historical demand is compared with the new demand after the implementation of the project, with satisfactory results.